Virus Structure and The Hypotheses Regarding Their Origin - M. Toshtemirova; M. Sobirjonova (Scientific Trends, 2025)
This paper explores the structural organization of viruses and the primary hypotheses regarding their origin. Viruses are acellular entities composed of a nucleic acid genome enclosed by a protein capsid, and sometimes a lipid envelope. Their structural simplicity belies a remarkable ability to infect and replicate within host cells. The article reviews three main theories of viral origin: the regressive hypothesis, suggesting viruses evolved from degenerate cells; the progressive hypothesis, proposing an origin from mobile genetic elements; and the virus-first hypothesis, asserting that viruses co-evolved with or even predated cellular life. The discovery of giant viruses has challenged traditional views and suggests a more complex evolutionary history. The paper concludes that while the origin of viruses remains uncertain, their impact on evolution, ecology, and biotechnology is profound and ongoing.
Keywords: Virus structure, virus vrigin hypotheses, virus evolution, capsid, nucleic acid, viral genome, giant viruses, regressive hypothesis, progressive hypothesis, virus-first hypothesis.